Perbandingan Perilaku Penggunaan QRIS dalam Aktivitas Konsumsi di Kalangan Mahasiswa - Nisa, Latifah Khairun; Alfatih, Yasmin Qalbi; Abdullah, Nasha Aulya; Jannah, Nailah Izzatul; Majid, Nur Cholik (Jurnal Bisnis, Manajemen, dan Ekonomi, 2025)
The presence of QRIS as a digital payment tool has provided convenience and speed in transactions, especially among the younger generation who are familiar with technology. This innovation supports the shift from conventional to digital payments. However, on the other hand, it also raises new challenges in the form of increased consumer behavior, especially among students. Ease of access to transactions through QRIS has the potential to encourage impulsive purchases, influenced by a digital lifestyle and developments in financial technology. Based on this phenomenon, this study aims to compare the consumer behavior of students from the Faculty of Economics and Business Education (FPEB) and the Faculty of Art and Design Education (FPSD) at the Indonesian University of Education in using QRIS. A quantitative approach with a comparative method was used in this study and supported by consumer behavior and decision-making theory as well as the Technology Acceptance Model (TAM). The sample was selected using quota sampling techniques based on certain criteria and purposive sampling with certain calculations, involving 50 FPEB students and 50 FPSD students who were active. Data were collected through a dichotomous questionnaire. The results showed that FPEB students tended to be better able to control their consumption and were less easily influenced by trends, while FPSD students were more technologically adaptable but more susceptible to consumerism due to external factors and technological conveniences. FPEB students tended to be better at information reception, decision-making, purchasing behavior, and perceived usefulness. Conversely, FPSD students were more efficient at processing information and more adaptable to technological conveniences such as QR codes, and external factors appeared relatively balanced between the two groups